CORRELATION AMONG POWER OF LIMB MUSCLES, FLEXIBILITY OF BACK MUSCLE AND DYNAMIC BALANCE WITH SMASH SKILL KEDENG ON SEPAKTAKRAW: (Correlation Study on Student BKMF Faculty of Sport Science, State University of Makassar) - Hasan (Jurnal Penjaskesrek, 2017)
This study aims to determine the correlation among the power of the limb muscles, the flexibility of back muscles and dynamic balance with kedengsmash skill on sepaktakraw. The research was conducted in the gymnasium of sepaktakrawFIK UNM Makassar South Sulawesi in March 2017. The sample of the study is 38 students of BKMF sepaktakrawFIK UNM. This method used in this study isan associative quantitative descriptive method with multiple correlation analysis models. The collecting data uses test and measurement techniques as a primary data through some tests, namely smash kedeng skill test, power of limb muscle test, flexibility of back muscles test and dynamic balance test. The results of this sudy finds that (1) there is a positive correlation between the power of limb muscle (X1) and the kedengsmash skill with the level of correlation of 0.875 and the coefficient of determination (r2) of 76.5; (2) there is a positive correlation betweenthe flexibility of back muscles (X2) and the kedengsmash skill (Y) with a correlation of 0.796 and the coefficient of determination (r2) of 63.4; (3) there is a positive correlation betweenthe dynamic balance (X3) and the kedengsmash skill (Y) with a correlation of 0.782 and the coefficient of determination (r2) of 61.1; and (4) there is a positive correlation among the power of limb muscle (X1), the flexibility of back muscle (X2) and the dynamic balance (X3) in all with the skill of kedengsmash (Y) with a correlation of 0.845 and the coefficient of determination (r2) of 71.4.